Analysis of Consumer Confidence on Mobile Commerce in Indonesia - Andhika Prabawati; I Putu Widyana; Suyoto Suyoto (IAES Indonesia Section, 2018)
The rapid development of mobile-based information technology, can change an existing business process. Such as loss of distributors in a single chain of business processes. Mobile Commerce industry is getting a good condition to grow. With the decrease in Mobile communication costs, more and more people are using mobile computing devices that can connect to the Internet. There are several m-Commerce applications in Indonesia, namely Lazada, Tokopedia, Buka Lapak, Shoppee and etc. The existence of these applications in Indonesia traders switch to online stores. This study takes three examples of m-Commerce applications in Indonesia with the top three criteria in terms of the best reviews and the highest number of reviews. The results of the sampling application is Lazada, Tokopedia and Buka Lapak. The process of collecting data taken will be analyzed to know about the level of consumer confidence in an m-Commerce application. This is evidenced by a collection of examples of online stores that exist in m-Commerce applications that inform ratings, discount information and existing features. The results obtained from this research is, consumer confidence can be seen from the review feedback that exist in each - each m-Commerce. Many discounts and low prices have no effect on consumer buying interest in the online store. The researcher's suggestion is to reward the most traded buyers with points that can be redeemed for certain goods, discounted goods or subsidized postage.